Influence of relationship marketing on cross buying in Malaysian mobile service sector - Abu, Mimi Liana (2012)
Relationship marketing has been widely considered as a company’s activity that not merely helps in acquiring new customers, but also to retain them in the company. It is well-known fact that the cost to entice a new customer is much higher than to maintain the current one. Additionally, it is said that high quality of relationship marketing is potentially able to increase relationship extension such as cross buying. While relationship marketing may influence customer to make additional purchases, however there is little agreement on which mediators could be used to achieve this aim. This study develops a model of relationship marketing based on existing literature to empirically investigate: (i) the influence of relationship marketing on customer satisfaction and loyalty; (ii) the influence of customer satisfaction on loyalty; and (iii) the ultimate influences of customer satisfaction and loyalty on cross buying. Specifically,this study aims to examine the direct and indirect influences of relationship marketing on cross buying, while taking into account the mediation effects of customer satisfaction and loyalty. Six underlying dimensions are employed in measuring relationship marketing, which are trust, commitment, communication, conflict handling, bonding and empathy. A sample of 300 customers was drawn using Mall Intercept Scientific Procedures in Klang Valley. Confirmatory Factor Analysis (CFA) is used to assess the unidimensionality of each dimension before the Structural Equation Model (SEM) is utilized to test five proposed hypotheses. The results show that all the hypotheses are supported thus providing evidence of significant direct and indirect influences of relationship marketing on cross buying. That means, cross buying can happen without the existence of customer satisfaction and loyalty, but the total influence (direct and indirect) of relationship marketing is more powerful. Based on the findings, this study gives an idea of synergistic of relationship marketing, customer satisfaction and customer loyalty in influencing cross buying. Therefore, it is imperative for practitioners and theorists to understand that relationship marketing is not merely important in satisfying and maintaining customers, but it helps in relationship enhancement as well.